2018
DOI: 10.4149/neo_2018_170726n504
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: an alternative pathway in GISTs tumorigenesis

Abstract: Many diseases have different pathological backgrounds responsible for abnormal cell behavior and exhibiting altered function and signal transduction. This is especially true for tumors and although changes affecting DNA sequence, irreversible mutations and chromosomal aberrations in gastrointestinal stromal tumors (GISTs) have been widely studied, the importance of reversible epigenetic changes increasingly recognized in many cancers has received insufficient attention in these tumors. Epigenetic mechanisms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 163 publications
(328 reference statements)
0
8
0
Order By: Relevance
“…Other agents are under study in clinical trials, including rogaratinib (potent and selective pan-FGFR inhibitor/NCT04595747), vandetanib (potent VEGFR inhibitor/NCT02015065), and guadecitabine (DNA methyl transferase inhibitor/NCT03165721). In addition, DNA hypomethylating agents are being evaluated in SDH-deficient GISTs, which may be associated with DNA hypermethylation [ 106 ].…”
Section: Molecular Classification Of Gistsmentioning
confidence: 99%
“…Other agents are under study in clinical trials, including rogaratinib (potent and selective pan-FGFR inhibitor/NCT04595747), vandetanib (potent VEGFR inhibitor/NCT02015065), and guadecitabine (DNA methyl transferase inhibitor/NCT03165721). In addition, DNA hypomethylating agents are being evaluated in SDH-deficient GISTs, which may be associated with DNA hypermethylation [ 106 ].…”
Section: Molecular Classification Of Gistsmentioning
confidence: 99%
“…Histopathological, molecular, genetic, and genomic studies have demonstrated that young women with BC show an increased rate of more aggressive subtypes with an overall worse prognosis, increased genetic susceptibility, differential tumor gene expression, specific genomic signatures, as well as alternations in epigenetic events including miRNA expression in comparison with postmenopausal women with BC [46]. Advances in novel technologies such as next-generation sequencing (NGS) and gene microarray have resulted in enormous progression and deluge sequence data about gene polymorphisms or determination of patterns of gene expression implicated in various pathological states [47,48,49,50]. Rummel et al [50] enrolled female patients within the Clinical Breast Cancer Project between 2001 and 2015 that were diagnosed with invasive BC before the age of 40.…”
Section: Pathological Characteristics and Tumor Behaviormentioning
confidence: 99%
“…In combination with the detection of DNA methylation status in other tumor suppressor genes (TSGs) (i.e., AOX1, APC, EDNRB ), the sensitivity of a prostate cancer diagnosis substantially increases [19,20]. Studies using DNA methylation as a prognostic biomarker have identified several aggressive tumors with an increased risk of rapid progression and/or relapse (RASSF1 in breast, prostate, squamous cervical cancer; CDH1 in squamous cervical cancer; APC in breast cancer; CDH1 in squamous cervical cancer; CDKN2A in colorectal cancer) [19,21,22]. DNA methylation in certain genes could also represent an excellent biomarker for predicting the response to a treatment.…”
Section: The Role Of Dna Methylation Patterns As Potential Diagnosmentioning
confidence: 99%
“…However, the altered methylation profile of many TSG promoter regions appears to have multiple functions as methylation markers: For example, the hypermethylation of the BRCA1 repair gene should serve as (i) a diagnostic marker where a methylation signature is proposed to predict a sporadic risk of developing breast cancer in BRCA1 mutation carriers; (ii) a prognostic marker that stratifies and predicts death in advanced diagnosis; (iii) a therapeutic marker that is also suggested to determine the sensitivity of breast and ovarian cancer to a cross-linking agent [19,20]. LINE-1 is often considered a surrogate pattern for global DNA methylation, and its overexpression caused by promoter hypomethylation leads to a less favorable prognosis in non-smallcell lung carcinoma and gastrointestinal stromal tumors [22,24].…”
Section: The Role Of Dna Methylation Patterns As Potential Diagnosmentioning
confidence: 99%